Study of the Sorption of Divalent Metal Ions on to Peat - Y.S. Ho; G. McKay; D.A.J. Wase; C.F. Forster (Adsorption Science & Technology, 2000)
A pseudo-second order rate equation describing the kinetics of sorption of divalent metal ions on to sphagnum moss peat at various initial metal ion concentrations and peat doses has been developed. The sorption kinetics were followed based on the concentrations of metal sorbed at various time intervals. Results show that chemical sorption processes might be rate-limiting for the sorption of divalent metal ions on to peat during agitated batch contact time experiments. The rate constant, the equilibrium sorption capacity and the initial sorption rate were calculated. From these parameters, an empirical model for predicting the concentrations of metal ions sorbed was derived.